Dynamic interplay between photodamage and photoprotection in photosystem II. (17th January 2018) - Townsend, Alexandra J.; Ware, Maxwell A.; Ruban, Alexander V.
Abstract: Photoinhibition is the light‐induced reduction in photosynthetic efficiency and is usually associated with damage to the D1 photosystem II (PSII) reaction centre protein. This damage must either be repaired, through the PSII repair cycle, or prevented in the first place by nonphotochemical quenching (NPQ). Both NPQ and D1 repair contribute to light tolerance because they ensure the long‐term maintenance of the highest quantum yield of PSII. However, the relative contribution of each of these processes is yet to be elucidated. The application of a pulse amplitude modulation fluorescence methodology, called protective NPQ, enabled us to evaluate of the protective effectiveness of the processes. Within this study, the contribution of NPQ and D1 repair to the photoprotective capacity of Arabidopsis thaliana was elucidated by using inhibitors and mutants known to affect each process. We conclude that NPQ contributes a greater amount to the maintenance of a high PSII yield than D1 repair under short periods of illumination. This research further supports the role of protective components of NPQ during light fluctuations and the value of protective NPQ and qPd as unambiguous fluorescence parameters, as opposed to qI and F v / F m, for quantifying photoinactivation of reaction centre II and light tolerance of photosynthetic organisms. Abstract : Protective nonphotochemical quenching (NPQ) of chlorophyll fluorescence as well as photosystem II reaction centre repair processes contributes to light tolerance of plants. However, the relative contribution of each of these processes is not known for short‐term illumination. Here, we applied the novel fluorescence methodology, called protective NPQ, that enabled evaluation of the contribution of these processes to light tolerance of the photosynthetic membrane and found that NPQ contributes a greater amount than D1 repair, but this contribution depends upon the light treatment and the NPQ capacity of the plant.